2015
DOI: 10.1088/1009-0630/17/10/09
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Main Phase of Ion Separation in the Process of Plasma-Optical Mass Separation

Abstract: This paper presents separation results of a mixture of nitrogen, argon and krypton ions in the process of plasma-optical mass separation on the POMS-E-3 separator model. We determined the behavior of the separation with a change in the value of magnetic field induction in the azimuthator and in the degree of compensation of the spatial charge in ion flows. An analysis is performed for experimental data by correlation with the results of a theoretical study and numerical experiments. The objectives of future ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Among the objectives of the investigations is the generation of a multi-component ion beam. The device used for beam generation is a two-chamber plasma accelerator with an anodic layer, PAAL (with a cold cathode) [32]. The second PAAL chamber also serves as the azimuthator, which is represented by the region with an applied radial (transverse to the ion velocity) magnetic field (up to 0.5 T); when passing through it, the ions with different masses acquire different azimuthal velocities, i.e.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…Among the objectives of the investigations is the generation of a multi-component ion beam. The device used for beam generation is a two-chamber plasma accelerator with an anodic layer, PAAL (with a cold cathode) [32]. The second PAAL chamber also serves as the azimuthator, which is represented by the region with an applied radial (transverse to the ion velocity) magnetic field (up to 0.5 T); when passing through it, the ions with different masses acquire different azimuthal velocities, i.e.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…Additionally, an intermediate range of masses (m ∼ m * ) can be collected axially by choosing the device length appropriately 72 . Experiments on this device using a mixture of three gases revealed that the flow becomes positively charged when going through the azimuthator, which in turn affects the ion dynamics and separation 73 . This observation was recently explained through analytical models for electron and ion flows in the azimuthator 74 .…”
Section: B Crossed-field In Non-magnetized Ion Regimementioning
confidence: 99%
“…There are three possible applications of low-resolution plasma mass separation: (a) RW disposal [21,22]; (b) SNF reprocessing [23][24][25][26][27]; and (c) rare earth elements recycling [28]. Previously, several experimental efforts were made aimed at the plasma separation of gases [29][30][31] and metals [32,33] in charge-neutral plasmas.…”
mentioning
confidence: 99%